How Corporate Governance Practices Affect the Cost of Debt: A Cross-Country Comparison of Pakistan and India - Nazir, Muhammad Umair (Jurnal Ilmiah Akuntansi dan Bisnis, 2021)
This study empirically examines the association between corporate governance practices and the cost of debt in Pakistan and India. By law, both Pakistani and Indian firms are required to publish their annual reports with recommended Corporate Governance Codes. Corporate governance practices were pivotal in the U.S. stock market crash of 1929. In this study, we used data from 2014 to 2017 of published compliance from 100 nonfinancial companies in Pakistan and India. This study discloses the essentiality of better corporate governance to decrease the cost of debt and offers additional empirical evidence through a comparative analysis of the links between corporate governance and the cost of debt in Pakistan and India. Keywords : corporate governance, cost of debt, Pakistan, India